Prevalence of and risk factors for anxiety after coronary heart disease: Systematic review and meta-analysis. Issue 38 (September 2019) - Chen, Ying-Ying; Xu, Ping; Wang, Yuan; Song, Tian-Jiao; Luo, Nan; Zhao, Li-Jing
Abstract: Background: As the most important component of cardiovascular disease, coronary heart disease (CHD) is closely related to psychological factors such as anxiety. Anxiety, whether present before or after the onset of illness, can lead to many serious consequences. The aim of this systematic review and meta-analysis was to assess the prevalence of and potential risk factors for anxiety after coronary heart disease (post-CHD anxiety). Method: Systematic searches were performed in electronic databases including China National Knowledge Infrastructure (CNKI), Wanfang, Technology Journal database (VIP), PubMed, Web of Science, Embase and Medline. Result: Thirteen studies were included. With regard to cross-sectional studies, the prevalence of post-CHD anxiety was P  = .37, 95% CI (0.26–0.49). The overall analysis among cohort studies revealed that the prevalence of post-CHD anxiety was P  = .50, 95% CI (0.05–0.95). Among the 11 potential risk factors, low education level [OR = 1.46, 95% CI (1.05–2.02)] and long duration of disease [OR = 2.05, 95% CI (1.05–4.00)] were statistically significant. Conclusion: There is high heterogeneity between studies and many defects; thus, further research is required to support these results. Attention should be paid to post-CHD anxiety, and clinical caring should include psychological counselling and imparting disease-related knowledge to patients with a long disease duration and low educational background. Abstract : Supplemental Digital Content is available in the text